Ideological integration in higher education: Insights from Indonesia’s leading state universities - Pabbajah, Mustaqim; Juhansar; McKenna, Tarquam; Widyanti, Ratri Nurina; Widyatmoko, Widi Fajar (Journal of Interdisciplinary Studies in Education, 2026)
Growing concerns over declining character values among Indonesian university students drive this study, which asserts that ideology-based character development model at two prominent public universities effectively enhance student integrity, ethics, and social responsibility. By analyzing these institutional strategies through interviews and document analysis, the research highlights how leadership values, social responsibility, and integrity are strengthened via ideology-based model. The findings indicate that these models boost ethical awareness and leadership skills, embedding national values in campus life. The study urges further research to validate these findings and provides universities with actionable guidance on reinforcing student character in the age of digital transformation.